#1. Simplify the expression 5+8(3+x) #2. Simplify the expression x+3+5x #3. Simplify the expression 5(z+4)+5(2-z)​

Question

#1. Simplify the expression 5+8(3+x)

#2. Simplify the expression x+3+5x

#3. Simplify the expression 5(z+4)+5(2-z)​

in progress 0
Xavia 5 months 2021-08-17T07:50:26+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-17T07:51:32+00:00

    1.) 29+8x
    2.)6x+3
    3.) 30

    0
    2021-08-17T07:52:00+00:00

    Answer:

    brainliest plssssss

    Step-by-step explanation:

    #1 Simplify the expression 5+8(3+x)

    Let’s simplify step-by-step.

    5+8(3+x)

    Distribute:

    =5+(8)(3)+(8)(x)

    =5+24+8x

    Combine Like Terms:

    =5+24+8x

    =(8x)+(5+24)

    =8x+29

    #2. Simplify the expression x+3+5x

    Let’s simplify step-by-step.

    x+3+5x

    Combine Like Terms:

    =x+3+5x

    =(x+5x)+(3)

    =6x+3

    #3. Simplify the expression 5(z+4)+5(2-z)​

    Let’s simplify step-by-step.

    5(z+4)+5(2−z)

    Distribute:

    =(5)(z)+(5)(4)+(5)(2)+(5)(−z)

    =5z+20+10+−5z

    Combine Like Terms:

    =5z+20+10+−5z

    =(5z+−5z)+(20+10)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )